The Implementation Of Jigsaw Technique In Teaching Writing Descriptive Text To The Seventh Grade Students Of MTs N Sidorejo In The Schooling Year Of 2011/2012 - Fitrianingtyas, Rani Nur (2012)
The object of this research is the teaching learning process by using jigsaw technique in teaching writing descriptive text. The writer describes the implementation of jigsaw technique in teaching writing descriptive text to the seventh grade student of MTs N Sidorejo. The objective of the study is describe the implementation of jigsaw technique in teaching writing descriptive text, describe the advantages of jigsaw technique, and describe the disadvantages of jigsaw technique in teaching writing descriptive text. This is a descriptive qualitative research. The writer uses descriptive qualitative research to make accurate and systematic description concerning with the implementation of jigsaw technique in teaching writing descriptive text. The methods of collecting data are interview, observation and documentation. The data in this research are analyzed by using qualitative analysis. The result of the study shows that. The implementation of jigsaw technique is appropriate with the theory. In the implementation of jigsaw technique the teacher uses three steps namely grouping, sharing, and writing. The advantages of jigsaw techniques are the student are more active, creative, enjoyed in teaching learning process. They also fell free to express their ideas. There are also have some disadvantages as follows, it spends much time, the classroom activity not maximal, and the class became noisy.